ITS DNA barcoding for species authentication of Thai arrowroot (Maranta arundinacea) and related Marantaceae - APHIDECH SANGDEE; THANWANIT THANYASIRIWAT; JUTHAPORN SAENGPRAJAK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sangdee A, Thanyasiriwat T, Saengprajak J. 2026. ITS DNA barcoding for species authentication of Thai arrowroot (Maranta arundinacea) and related Marantaceae. Biodiversitas 27 (3): d270332. https://doi.org/10.13057/biodiv/d270332. Maranta arundinacea (arrowroot) is an underutilized starch-producing crop whose taxonomic identification is often constrained by overlapping vegetative characters, pronounced phenotypic plasticity, and the frequent absence of diagnostic reproductive structures during dormancy. These factors complicate species identification and germplasm authentication within Maranta and related Marantaceae taxa. This study evaluated the effectiveness of nuclear ribosomal Internal Transcribed Spacer (ITS) DNA barcoding for identifying arrowroot and distinguishing closely related taxa in Thailand. ITS sequences were obtained from Maranta samples collected across several geographic regions, with Goeppertia ornata included for comparison. Phylogenetic relationships were inferred using maximum likelihood analysis. All M. arundinacea accessions showed high ITS sequence similarity and clustered into a single well-supported lineage, indicating genetic uniformity consistent with long-term vegetative propagation. In contrast, ITS variation enabled clear discrimination among other Maranta species that are difficult to distinguish morphologically. Phylogenetic analysis resolved distinct lineages within Maranta and recovered G. ornata as a separate lineage, supporting its classification as a distinct genus. These results demonstrate that ITS DNA barcoding is an effective tool for species authentication, phylogenetic analysis, and germplasm verification, and provide a molecular basis for future conservation and sustainable utilization of arrowroot resources in Thailand.